The Impact of Satisfaction and Trust on Loyalty of E-Commerce Customers - Brilliant, Mochammad Auditya; Achyar, Adrian (ASEAN Marketing Journal, 2021)
The number of Internet users in Indonesia and e-commerce sales is growing. However, Indonesia is less active in e-commerce research compared to other Asian countries, and existing studies cover limited area. The purpose of this study is identifying the impact of customer satisfaction and trust on loyalty in e-commerce and identifying the factors that influence satisfaction. The results are that information quality affects trust and that trust affects loyalty. E-commerce websites should focus on delivering trusted information on product quality, which will lead to greater customer trust, and greater trust will lead to greater loyalty to the websites